The Roles of Health Assistants, Nursing Technicians and Public Health Professionals in Advancing Healthcare Services: Responsibilities, Challenges, and Future Perspectives - Mohammed Falji Alanazi, ALOTAIBI, MESHAAL MOHAISEN M, Homoud Falji Alanazi, Majed Barjas Alanazi, Jayez Meshaal Alenazi, Maryam Hezamalenazi; Nawal Hanif Dahi Alanazi, Sultan Mohammed Alsubae, MUHAYLAN RAJA MUHAYLAN ALANAZI, WAIL QRAYAN R ALANAZI (Journal of International Crisis and Risk Communication Research, 2024)
This paper explores the critical roles of health assistants, nursing technicians, and public health professionals in advancing healthcare services. These professionals play an essential role in providing quality healthcare, improving patient outcomes, and ensuring the sustainability of healthcare systems globally. The paper outlines their core responsibilities, identifies the challenges they face, and discusses future perspectives on how these roles can evolve to meet the increasing demands of healthcare delivery. It emphasizes the importance of collaboration, continuing education, and policy development in strengthening these workforce segments to support the advancement of healthcare services worldwide.